2022
DOI: 10.1177/00405175221137351
|View full text |Cite
|
Sign up to set email alerts
|

Study on yellowing mechanism and inhibiting technology based on amide salts modified polyester

Abstract: Terephthalic acid and ethylene glycol were used to prepare poly(ethylene terephthalate)-co-amide salts with adipate pentamethylenediamine (AP salts) as the modified monomer, improving the hygroscopicity and softness of poly(ethylene terephthalate) fibers. One of the facets of concern is that the yellowing index of poly(ethylene terephthalate)-co-amide salts increases from 3.8 to 13.8 than poly(ethylene terephthalate) and increases from 2.9 to 11.7 for fibers, limiting its acceptance in textile applications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The PL spectra of LPGSQ64 films doped with 100% Eu, 100% Tb, and a 50% Eu/50% Tb mixture indicated that energy transfer occurs from Tb 3+ to Eu 3+ (Figure S3) , consistent with a previous work by Cui et al [ 35 ]. Furthermore, the PL spectra showed that the intensity of Tb 3+ emission in the LPGSQ64–Tb film decreased by approximately 88% in the LPGSQ64–Eu:Tb (1:1) film, whereas the intensity of Eu 3+ emission in the LPGSQ64–Eu film decreased by only 46% in the LPGSQ64–Eu:Tb (1:1) film.…”
Section: Resultssupporting
confidence: 90%
“…The PL spectra of LPGSQ64 films doped with 100% Eu, 100% Tb, and a 50% Eu/50% Tb mixture indicated that energy transfer occurs from Tb 3+ to Eu 3+ (Figure S3) , consistent with a previous work by Cui et al [ 35 ]. Furthermore, the PL spectra showed that the intensity of Tb 3+ emission in the LPGSQ64–Tb film decreased by approximately 88% in the LPGSQ64–Eu:Tb (1:1) film, whereas the intensity of Eu 3+ emission in the LPGSQ64–Eu film decreased by only 46% in the LPGSQ64–Eu:Tb (1:1) film.…”
Section: Resultssupporting
confidence: 90%